Islamic Criminal Law’s View on The Crime of Attempted Rape - Ramadhani, Putri (Universitas Islam Negeri Sumatera Utara, 2023)
The view of Islamic Pidama Law on the crime of attempted rape is a concept that reflects the values of justice, protection of individuals, and law enforcement in Islam. The interpretation and handling of the crime of attempted rape in the context of Islamic law is influenced by the principles of sharia based on the Qur'an and Hadith. In cases of attempted rape, Islamic law emphasizes that the perpetrator must be tried fairly and strictly in accordance with the applicable law. This includes careful investigation, collection of sufficient evidence, as well as the enforcement of sanctions appropriate to the level of wrongdoing committed. In the context of Islamic criminal law, the crime of attempted rape is considered a serious offense against social order and moral norms. Therefore, law enforcement in such cases must be carried out with great care and justice. The sanction given to the perpetrator must be balanced with the level of guilt, taking into account aspects of mitigation and rehabilitation. In addition, in the view of Islamic Penal Law, it is important to provide adequate protection and support to victims of attempted rape. This includes access to medical care, psychological support, and efforts to restore the victim's dignity and confidence. Islamic law emphasizes the importance of providing justice to victims and ensuring that their rights are not overlooked in the legal process. In practice, the Islamic Penal Code's view of the crime of attempted rape is often implemented through a justice system based on Islamic law or through legal institutions that have a mandate to uphold Islamic values in law enforcement. Prevention efforts are also emphasized in public education and awareness about the importance of respecting individual rights and maintaining moral integrity in social relations. Thus, the Islamic Penal Code's view of the crime of attempted rape underscores a commitment to justice, the protection of human rights, and the fair enforcement of the law. In handling such cases, the principles of Islamic law are implemented to maintain security and peace in society and provide appropriate protection for individuals who are vulnerable to becoming victims.